Co-Expression of Runx1, Hoxa9, Hlf, and Hoxa7 Confers Multi-Lineage Potential on Hematopoietic Progenitors Derived From Pluripotent Stem Cells - Yu, Bo; Wu, Bingyan; Hong, Pingshan; Peng, Huan; Zhang, Mengyun; Zhang, Qi; Liu, Lijuan; Liu, Xiaofei; Geng, Yang; Wang, Jinyong; Lan, Yu (Frontiers in Cell and Developmental Biology, 2022)
The intrinsic factors that determine the fundamental traits of engraftment ability and multi-lineage potential of hematopoietic stem cells (HSCs) remain elusive. The induction of bona fade HSCs from pluripotent stem cells (PSCs) in dishes is urgently demanded but remains a great challenge in translational medicine. Runx1, Hoxa9, Hlf, and Hoxa7 are developmentally co-expressed during endothelial-to-hematopoietic transition and adult haematopoiesis. However, the expression of these factors fails to be turned on during in vitro hematopoietic induction from PSCs. Here, we established an inducible gene over-expression embryonic stem cell (ESC) line in which exogenous Runx1, Hoxa9, Hlf, and Hoxa7 genes were tandemly knocked in. A population of induced hematopoietic progenitor cells (iHPCs) expressing Kit and Sca1 surface markers were successfully obtained in vitro from the gene edited-ESC line. Upon transplantation of the Runx1-Hoxa9-Hlf-Hoxa7 ESC-derived iHPCs into irradiated immunodeficient mice, they can dominantly contribute to B cells, low proportions of T cells and myeloid cells. However, Runx1-Hoxa9-Hlf ESC-derived iHPCs only produced B lineage cells with extremely low contributions. Our study unveils that the coordination of Runx1, Hoxa9, Hlf, and Hoxa7 led to generation of the hematopoietic progenitors with the capacity of multi-lineage hematopoietic reconstitution in the immunodeficient recipient mice.